Application of the National Early Warning Score (NEWS) as a stratification tool on admission in an Italian acute medical ward: A perspective study. Issue 3 (9th March 2017) - Spagnolli, Walter; Rigoni, Marta; Torri, Emanuele; Cozzio, Susanna; Vettorato, Elisa; Nollo, Giandomenico
Summary: Aim: We aimed to assess the performance of the National Early Warning Score (NEWS) as tool for patient risk stratification at admission in an acute Internal Medicine ward and to ensure patient placement in ward areas with the required and most appropriate intensity of care. As secondary objective, we considered NEWS performance in two subgroups of patients: sudden cardiac events (acute coronary syndromes and arrhythmic events), and chronic respiratory insufficiency. Methods: We conducted a perspective cohort single centre study on 2, 677 unselected patients consecutively admitted from July 2013 to March 2015 in the Internal Medicine ward of the hospital of Trento, Italy. The NEWS was mandatory collected on ward admission. We defined three risk categories for clinical deterioration: low score (NEWS 0‐4), medium score (NEWS 5‐6), and high score (NEWS≥7). Following adverse outcomes were considered: total and early (<72 hours) in‐hospital mortality, urgent transfers to a higher intensity of care. A logistic regression model quantified the association between outcomes and NEWS. Results: For patients with NEWS >4 vs patients with NEWS <4, the risk of early death increased from 12 to 36 times, total mortality from 3.5 to 9, and urgent transfers from 3.5 to 7. In patients with sudden cardiac events, lower scores were significantly associated with higher risk of transfer to a higher intensity of care. In patients affected by chronic hypoxaemia, adverse outcomes occurred less in medium and high score categories of NEWS. Conclusions: National Early Warning Score assessed on ward admission may enable risk stratification of clinical deterioration and can be a good predictor of in‐hospital serious adverse outcomes, although sudden cardiac events and chronic hypoxaemia could constitute some limits.